EFFECT OF GLUTATHIONE ON MDA (MALONDYALDEHIDE) PLASMA AND SOD (SUPEROXYDE DYSMUTASE) ERYTHROCYTE ON WHITE RAT ( RATTUS NORVEGICUS ) INDUCED BY PARACETAMOL - Liza Yudistira Yusan; Karma Budiman; Choesnan Effendi (JOURNAL OF PHARMACY SCIENCE AND TECHNOLOGY, 2021)
Glutathione has a role to neutralize free radicals and reactive oxygen compounds, as well as to maintain exogenous antioxidants. Indicators to show the side effect of paracetamol is elevation of transaminase enzymes in plasma. The increase of free radicals is indicated by an increase in MDA (Malondyaldehide) and a decrease in SOD (Superoxyde Dysmutase). The aim of the study is to know the effects of external gluthathion on MDA and SOD levels in rats induced by Paracetamol (PCT). This study used four groups for each treatment : the first group (only given food standards); The second group (fed standard plus PCT); The third group (fed standard plus PCT and GSH dose of 600 mg / kg); The fourth group (fed standard plus PCT and GSH dose of 1200 mg / kg). GSH reduced significantly MDA plasma level (p=0,004), but in SOD level there is no differences among these groups. In our conclusion, GSH can be used alternatively to minimize the toxic effects of Paracetamol